Tailorable negative permittivity of graphene-carbon nanotube/copper calcium titanate metacomposites. Issue 7 (1st April 2021) - Ma, Rongwei; Cheng, Chuanbing; Qu, Yunpeng; Fan, Runhua
Abstract: Ceramic metacomposites have been substantially investigated to obtain negative permittivity owing to their promising applications in electronics and dielectric devices. However, the modulation of negative permittivity has still been a challenging issue to be investigated. Herein, CaCu3 Ti4 O12 (CCTO) ceramic nanocomposites with varying content of graphene-carbon nanotube (GR-CNT) fillers were fabricated. There are two different types of radio-frequency (RF) negative permittivity in GR-CNT/CCTO metacomposites, i.e. induced dielectric resonance and plasma oscillation, which provided original envisage for tailorable negative permittivity. Resonance-type negative permittivity behavior originated from the abundant electric dipoles in the isolated GR-CNT clusters and interfacial polarization between GR-CNT and CCTO. Strongly dispersion of negative permittivity (~-10 4 ) was achieved in the metacomposites with high carbon content, which was ascribed to plasmonic state of extensive free carriers in percolating GR-CNT networks. Weakly negative permittivity (~-10 2 ) was obtained in the composites above the epsilon-near-zero frequencies, which were ~860 MHz, ~430 MHz and ~370 MHz, respectively. Inductive character of metacomposites was an intrinsic performance exactly as equivalent circuit analysis demonstrated. This work benefits for clarifying the regulation mechanism of negative permittivity, which can pave the way to expand the applications of ceramic composites in the field of metamaterials.